Acid Test ECJ: Undermine or strengthen co-determination? - Lasse Pütz; Sebastian Sick (Hans-Böckler-Stiftung, 2015)
- Based on a question submitted by a German court of law, the ECJ has to decide whether the existing laws on employee participation in company bodies, respectively their application, are compatible with European law. - Depending on the decision reached by the ECJ there is a threat of considerable upheavals within the national systems of industrial relationships in all Member States. Consequently, the proceedings have substantial significance extending far beyond Germany's borders. - The governments of the EU Member States can participate in the proceedings before the ECJ with their own opinions. The national federations of trade unions should examine whether, with regard to the points of view stated, it is meaningful to campaign to their own national governments for the submission of an individual position statement.
Keywords: 330